Identifying Risk and Resilience Factors in the Intergenerational Cycle of Maltreatment: Results From the TRANS-GEN Study Investigating the Effects of Maternal Attachment and Social Support on Child Attachment and Cardiovascular Stress Physiology - Buchheim, Anna; Ziegenhain, Ute; Kindler, Heinz; Waller, Christiane; Gündel, Harald; Karabatsiakis, Alexander; Fegert, Jörg (Frontiers in Human Neuroscience, 2022)
Introduction: Childhood maltreatment (CM) is a developmental risk factor and can negatively influence later psychological functioning, health, and development in the next generation. A comprehensive understanding of the biopsychosocial underpinnings of CM transmission would allow to identify protective factors that could disrupt the intergenerational CM risk cycle. This study examined the consequences of maternal CM and the effects of psychosocial and biological resilience factors on child attachment and stress-regulatory development using a prospective trans-disciplinary approach. Method: Mother-child dyads (N=158) participated shortly after parturition (t0), after 3 months (t1), and 12 months later (t2). Mothers’ CM experiences were assessed at t0, attachment representation at t1 and psychosocial risk and social support were assessed at t1 and t2. At t2, dyads participated in the Strange Situation Procedure (SSP). Children’s attachmen status were classified as organized vs. disorganized, including their level of disorganized behavior, and heart rate (HR) and respiratory sinus arrhythmia (RSA) were recorded as stress response measures of the autonomic nervous system. Maternal caregiving during SSP was assessed using the AMBIANCE scale. Child’s single nucleotide polymorphisms (SNP) rs2254298 within the oxytocin receptor (OXTR) and rs2740210 of the oxytocin gene (OXT) were genotyped using DNA isolated from cord blood. Results: Maternal CM experiences (CM+) was significantly associated with an unresolved attachment status, higher perceived stress and more psychological symptoms. These negative effects of CM were attenuated by social support. As expected, maternal unresolved attachment and child disorganized attachment were significantly associated. Maternal caregiving did not mediate the relationship between maternal and child attachment but influenced children’s HR and RSA response and disorganized behavior. Moreover, the rs2254298 genotype of the OXTR gene moderated the stress response of children from mothers with CM. Children carrying the rs2740210 risk allele of the OXT gene showed more disorganized behavior independent from maternal CM experiences. Conclusion: We replicated and extended existing CM and attachment models by co-examining maternal attachment, social support, and child genetic susceptibility on child attachment and cardiovascular stress regulation. The findings contribute to an extended understanding of risk and resilience factors and enable professionals to target adequate services to parents and children at risk